2002
DOI: 10.1081/cbi-120002914
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation in oxidative stress markers in healthy and type II diabetic men

Abstract: Seven clinically healthy, nondiabetic (ND) and four Type II diabetic (D) men were assessed for circadian rhythms in oxidative "stress markers." Blood samples were collected at 3h intervals for approximately 27 h beginning at 19:00h. Urine samples were collected every 3 h beginning with the 16:00h-19:00h sample. The dark (sleep) phase of the light-dark cycle extended from 22:30h to 06:30h, with brief awakening for sampling at 01:00h and 04:00h. Subjects were offered general hospital meals at 16:30h, 07:30h, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 26 publications
(34 reference statements)
2
79
4
Order By: Relevance
“…A study by Kanabrocki et al found that many byproducts of an increase in oxidative stress are regulated rhythmically in diabetics, stressing the importance of ROS levels. They found a marked circadian rhythm in DNA oxidation (in urine), uric acid (in serum), and nitric oxide (in serum) levels in nondiabetic men, but not in diabetic subjects (90). This study found that the peak levels of serum concentrations of the markers occurred in the early evening, suggesting a correlation between oxidative damage and increased metabolism.…”
Section: Diabetesmentioning
confidence: 61%
See 1 more Smart Citation
“…A study by Kanabrocki et al found that many byproducts of an increase in oxidative stress are regulated rhythmically in diabetics, stressing the importance of ROS levels. They found a marked circadian rhythm in DNA oxidation (in urine), uric acid (in serum), and nitric oxide (in serum) levels in nondiabetic men, but not in diabetic subjects (90). This study found that the peak levels of serum concentrations of the markers occurred in the early evening, suggesting a correlation between oxidative damage and increased metabolism.…”
Section: Diabetesmentioning
confidence: 61%
“…Several studies have shown evidence of differences in DNA damage, lipid peroxidation, and protein oxidation at different times of the day, thus indicating circadian oscillations of oxidative stress responses (51,90,97,100,176). These oscillations relate directly to the daily rhythm of antioxidant expression and protective enzyme activity levels (Fig.…”
Section: Rhythmicity Of the Cellular Antioxidant System: Patterns Of mentioning
confidence: 99%
“…plasma uric acid, melatonin, reduced thiols), and oxidatively-generated substrates (e.g. plasma malondialdehyde, urinary 8-OHdG) exhibit strong circadian or other temporal fluctuations in amount or activity (Bridges et al 1992a;Hardeland et al 2003;Kanabrocki et al 2002Kanabrocki et al , 2004Kanabrocki et al , 2000Luo et al 1997;Niklowitz et al 2006;Reiter et al 1996;Valencia et al 2001). Whether the afternoon peak in salivary protein carbonyls (present study) is due to diurnal deficiencies in salivary gland / orophayngeal antioxidant defenses or augmented ROS production remains unclear.…”
Section: Discussionmentioning
confidence: 84%
“…Oxidation of macromolecules within the body is part of normal homeostatic processes that regulate cellular signalling, growth and adaptations within tissues. Many lifestyle factors, including health history, nutritional status (Møller et al, 1996) and even internal circadian rhythm (Kanabrocki et al, 2002) can influence the degree of oxidative modification to these macromolecules. As a result, previous observational studies monitoring the impact of mental stress on markers of oxidative stress/ROS at one 'snap shot' warrant careful interpretation.…”
Section: Discussionmentioning
confidence: 99%